A POWERFUL ELISA TECHNIQUE TO TEST THE POTENTIAL OF EXTRA VIRGIN OLIVE OIL IN REDUCING TNF-Α LEVEL AND EDEMA VOLUME IN MALE Rattus norvegicus EXPOSED TO CARRAGEENAN - Andina Putri Aulia; Suprapto Maat; Aryati (Universitas Nahdlatul Ulama Surabaya, 2020)
Extra virgin Olive oil is extracted from fruit that can be used as anti-inflammatory agent. This research aimed to test the potential of extra virgin olive oil in reducing edema volume and TNF-α plasma in carrageenan-induced rats. This research was purely experimental research with the post test control group design. A total of twenty eight Wistar rats were divided randomly into four treatment groups. Group I was a control negative group, while the group II, III, and IV were orally administered with extra virgin Olive oil at the dose of 0.9 ; 1.8 ; 2.7 mL/day, respectively. Paw edema was measured one hour before the rats was induced to carrageenan and every hour until four hours after it was induced to carrageenan. TNF-α plasma was measured at four hours. Analysis of the data was done by calculating the presentation of edema inhibition in every group, then the data was statistically analyzed by Anova, Repeated Anova, LSD and Kruskal Wallis test with 95% confidence interval. The result showed that extra virgin olive oil has an anti-inflammatory effect. The highest decrease in edema volume percentage was in group III (14.21%). There was a significant difference in the edema volume of all treatment groups at each time of the experiment with TNF-α value (p < 0.05). In conclusion, the administration of extra virgin olive oil can lower the volume of carrageenan-induced edema in rats depend on the dose. Also, the administration of extra virgin olive oil can be dose-dependent in reducing the levels of TNF-α in carrageenan-induced edema in rats.